2022
DOI: 10.1098/rspb.2022.0851
|View full text |Cite
|
Sign up to set email alerts
|

Life-history genotype explains variation in migration activity in Atlantic salmon ( Salmo salar )

Abstract: One of the most well-known life-history continuums is the fast–slow axis, where ‘fast’ individuals mature earlier than ‘slow’ individuals. ‘Fast’ individuals are predicted to be more active than ‘slow’ individuals because high activity is required to maintain a fast life-history strategy. Recent meta-analyses revealed mixed evidence for such integration. Here, we test whether known life-history genotypes differ in activity expression by using Atlantic salmon ( Salmo salar ) as a model. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In more controlled, aquaculture, conditions, the influence of the vgll3 genotype on maturation age was observed in males, but not females (Ayllon et al., 2019 ). Furthermore, a study of movement activity in a semi‐natural environment observed increased movement activity in migrating females with the vgll3 *EE allele, whereas the vgll3 *LL allele was related to increased activity in males but no association with vgll3 genotype was observed for activity level in nonmigrating individuals (Niemelä et al., 2022 ). The apparent stronger influence of the vgll3 genotype in males in our study could potentially be explained by the fact that males often mature at a younger age than females (Barson et al., 2015 ), and males can mature in captivity already at 1 year of age (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In more controlled, aquaculture, conditions, the influence of the vgll3 genotype on maturation age was observed in males, but not females (Ayllon et al., 2019 ). Furthermore, a study of movement activity in a semi‐natural environment observed increased movement activity in migrating females with the vgll3 *EE allele, whereas the vgll3 *LL allele was related to increased activity in males but no association with vgll3 genotype was observed for activity level in nonmigrating individuals (Niemelä et al., 2022 ). The apparent stronger influence of the vgll3 genotype in males in our study could potentially be explained by the fact that males often mature at a younger age than females (Barson et al., 2015 ), and males can mature in captivity already at 1 year of age (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, given that Fjelldal et al (2018) showed no intrinsic developmental conflict in domesticated Atlantic salmon, and experimental trials on wild and hatchery fish in laboratories have shown that maturation and smolting can occur within the same year under stable conditions (Berglund et al, 1991(Berglund et al, , 1992Hansen et al, 1989;Lundqvist et al, 1988;Saunders et al, 1982), we also suggest that there exists no conflict between the two developmental pathways in the wild. Rather, environmental factors such as temperature and nutrient acquisition, along with genetic components (i.e., maturation genes such as vgll3; Åsheim et al, 2023;Niemelä et al, 2022) limit an individual's ability to undergo both energetically demanding process with the same 12month period.…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratory studies have now shown that temperature and food resource availability can increase the chances that maturity occurs in parr (Adams & Thorpe, 1989; Åsheim et al, 2023; Berglund et al, 1991; Debes et al, 2020; Thorpe, 1994). This is in part influenced by genetics, specifically the vgll3 gene which can encode for late or early maturity (Åsheim et al, 2023; Niemelä et al, 2022). Although the vgll3 gene was originally identified as a strong correlate with the number of years an individual spent at sea before returning to spawn (Barson et al, 2015), recent common garden experiments have shown that the gene may play a role in determining maturity pre‐smolting (Åsheim et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variation in vgll3 associates with maturation age in humans as part of a more complex genetic architecture that hinders genotype-phenotype dissection 23 . Genetic variation in vgll3 is associated with an ensemble of puberty-related traits in Atlantic salmon including age at maturity 14,22 , early male maturation [24][25][26] , body condition 25,27 , food acquisition preference 28 , aerobic performance 29 , aggressive behavior 30 , and migration behavior 31 . Although vgll3 may represent the most pleiotropic large-effect life-history gene yet found, the molecular mechanisms by which vgll3 genotypes have such pleiotropic effects on distinct phenotypes are not known.…”
Section: Introductionmentioning
confidence: 99%